Students’ perceptions of teachers’ beliefs and their effects on students’ achievement - Zaim, M; Refnaldi, Refnaldi; Kholis, Muhammad (Konselor, 2020)
Teachers’ beliefs are a personal construct that can provide understandings, perceptions, and evaluation of teachers' practices. The purpose of this research was to find out the students' perceptions toward teachers' beliefs and their effect on students' achievement in English as a general subject at Universitas Negeri Padang. This research was ex-post facto research. The students of English as a general subject in 2018/2019 academic year were the population of this study. The sample was chosen by using a random sampling technique in which there were 150 students chosen as the subjects of this research. The data were taken by using a Likert-scale questionnaire and analyzed by using SPSS Statistics 18 Software. The result showed that there were no significant effects of teachers' beliefs on students' achievement. H0 was accepted because the t-value was lower than the t-table. The value of the t-value was 1.008, while the t-table was 6.313.